The Song of the Stone Wall - Keller, Helen, 1880-1968 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Song of the Stone Wall" by Helen Keller is a poetic reflection written in the early 20th century. This work, which could be classified as a collection of poems, explores themes of nature, history, and the human experience as expressed through the metaphor of stone walls. The book likely aims to convey the significance of labor, perseverance, and the spiritual and emotional connections humans have with their environment and heritage. In the poem, Keller invites readers to walk with her alongside a stone wall, using it as a canvas to illustrate the labor and lives of those who built it. Through rich imagery and evocative language, she contemplates the history woven into the stones$1 (Bthe struggles, hopes, and dreams of the forefathers who shaped the land. She connects the physicality of the stones to deeper philosophical and spiritual truths, exploring themes of life, death, and rebirth. The walls are portrayed as silent witnesses to the trials of humanity, encapsulating the essence of the natural world while simultaneously reflecting the historical journey of the American spirit. Ultimately, the poem serves as a celebration of resilience, faith, and the beauty found in both nature and human endeavor. (This is an automatically generated summary.)s
Release date is 2004-04-01
Produced by Jamie Taylor in memory of Helen Keller
Keywords: American poetry -- 20th century